Immobilisation dose rates for Weddell seals during expedition ANT-Land_2024_SEAEIS (NEU2024) - Horst Bornemann; Henning Schröder; Christoph Held (PANGAEA, 2025)
Weddell seals (Leptonychotes weddellii) were immobilised during expedition ANT-Land_2024_SEAEIS (NEU2024) for the purpose of deployments with infrared (IR) camera loggers (CAM). The IR-CAM deployments (n=13) were located at Atka-Bay in the vicinity to the Neumayer Station III (DE), eastern Weddell Sea. The seals were searched by Skidoo on fast (bay) ice and captured along tidal cracks within the bay and immobilised and instrumented with infrared video camera loggers (Little Leonardo, JP) to investigate their foraging behaviour in the context of ROV-borne imagery and sea ice features within the Atka Bay.